Divorce in Norwegian same-sex marriages 1993-2011 - Kenneth Aarskaug Wiik; Ane Seierstad; Turid Noack (Statistics Norway, Research Department, 2012)
Using longitudinal register data, we first present updated descriptive statistics on the total population of same-sex registered partnerships and marriages formed 1993-2010. Second, we investigate the divorce risk of these couples through 2011 and expect to find that the changing composition of same-sex partnerships has lowered their higher divorce risk. Results show that same-sex couples had a higher risk of divorce compared with opposite-sex married couples and that female couples were significantly more divorce prone than male couples. We found no evidence that the gender gap in divorce or the difference between same-sex and opposite-sex couples have narrowed over time.
Keywords: J12; 330; Divorce; registered partnership; same-sex marriage